Gravitational mass flow measurements of various granular materials in relation to an extended Bond number. (April 2023) - Just, M.; Medina Peschiutta, A.; Hippe, F.; Useldinger, R.; Baller, J.
Abstract: Uniaxial die pressing is a commonly used shaping technique in powder metallurgy. The initial step within the compression cycle is the filling process of the cavity with granular materials. Here, the goal is to have a reproducible cavity filling to manufacture compressed parts of consistent quality. Besides effects linked to the geometry of the cavity and the mechanisms of filling, the flowability of the granular material plays a major role. Therefore, a deeper understanding of the flow behaviour is in the centre of the present study. In order to assess the flowability, two different experimental methods are used. Granular materials of the same composition but different granular size distributions are characterised by angle of repose (AOR) and mass flow rate measurements. The two methods deliver a set of parameters that are compared using the granular Bond number. Based on the empirical findings, a modification of the granular Bond number is suggested. Highlights: Effective friction coefficients increases with finer hard metal granules. Calculation of granular Bond numbers for hard metal granules based on a mixing rule. Mass flow rates of sieved granules are related to the granular Bond number. Scaling of the granular Bond number.